2016
DOI: 10.1111/cote.12193
|View full text |Cite
|
Sign up to set email alerts
|

Applications of natural dye from Ixora coccinea L. in the field of textiles and cosmetics

Abstract: In the present study an attempt has been made to propose the application of natural dye from Ixora coccinea L., commonly known as Jungle geranium, in the field of textiles and cosmetics. Dyeing with I. coccinea colourant with different combinations of mordants resulted in different shades, such as pink, lilac, and grey shades. The dyed samples were tested according to ISO standard test methods. The samples dyed with combinations of stannous chloride/ferrous sulphate and stannous chloride/ammonium ferrous sulph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…Several studies have shown that synthetic dyes in hair dyeing products may cause side effects such as mutagenicity, cancer, allergic reactions, and toxicity in the environment and for humans, whereas natural dyes are ecofriendly, biodegradable, less allergenic and have low levels of toxicity for humans [1]. Several studies have shown that synthetic dyes in hair dyeing products may cause side effects such as mutagenicity, cancer, allergic reactions, and toxicity in the environment and for humans, whereas natural dyes are ecofriendly, biodegradable, less allergenic and have low levels of toxicity for humans [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that synthetic dyes in hair dyeing products may cause side effects such as mutagenicity, cancer, allergic reactions, and toxicity in the environment and for humans, whereas natural dyes are ecofriendly, biodegradable, less allergenic and have low levels of toxicity for humans [1]. Several studies have shown that synthetic dyes in hair dyeing products may cause side effects such as mutagenicity, cancer, allergic reactions, and toxicity in the environment and for humans, whereas natural dyes are ecofriendly, biodegradable, less allergenic and have low levels of toxicity for humans [1].…”
Section: Introductionmentioning
confidence: 99%
“…The standards are usually designed to fade after given periods of time. The changes in colour of the coloured fabrics were evaluated by comparing with the blue scale for light fastness (1)(2)(3)(4)(5)(6)(7)(8). Colour fastness to rubbing was tested according to ISO 105 -X12 method [19].…”
Section: Colour Fastness Testmentioning
confidence: 99%
“…This has led to an increase in the demand for natural colourants by consumers. The use of natural colourants [4] in both textile and other non-textile uses is a way of supporting sustainable development with respect to health and safety in the environment [5][6][7][8]. Nature has an abundance of dye-yielding plants and animal species.…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle büyük oranda gelişen Kimya endüstrisinin etkisiyle, çevreyi en çok kirleten maddelerden birisi de boyar ham maddelerdir. Boyarmaddeler, birçok malzemenin renklendirilmesinde ve yüzey özelliklerinin geliştirilmesinde, ilaç sanayinde (Bazylevich, Patsenker, & Gellerman, 2017), dye lazerlerde elektro optik manyetik ışımanın dalga boyunu ayarlamada (Cyprych, Kopczyńska, Kajzar, Rau, & Mysliwiec, 2015), fotodinamik terapide (Kamkaew et al, 2013;Molupe et al, 2018), gıda ve kozmetik endüstrisinde (Patil & Datar, 2016) ve daha birçok alanda geniş kullanıma sahiptir. Endüstride kullanılan boyarmaddelerin birçoğu sentetiktir ve toksik etkisi, ciddi çevre ve sağlık sorunlarına yol açmaktadır.…”
Section: Introductionunclassified